Survey Analysis of Students and Teachers’ Perceptions of E-Learning and M-Learning in Morocco - Dehbi, Amine; Dehbi, Rachid; Bakhouyi, Abdellah; Talea, Mohamed (International Journal of Interactive Mobile Technologies (iJIM), 2023)
<span style="caret-color: #000000; color: #000000; font-family: Helvetica; font-size: 12px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; display: inline !important; float: none;">New technology, such as mobile phones and smart devices, has sparked the creation of new methods of learning. They are integrated into modern e-learning systems due to their rising popularity. E-learning and mobile learning provide students with more options for learning without any limitations. Today, many students are adapted to these new technologies as long as they have inherited a naturally tech-savy mindset. We use survey data to explore students and teachers’ interest in e-learning and mobile learning. This survey will help us discover the real value of these subjects in Moroccan higher education. Once we have collected our survey responses, we will be able to determine whether our study has had an impact on the students and teachers par- ticipation in these new forms of learning. At the end of the topic, all the answers and the statistics (quantitative and qualitative) that we have collected from our students and teachers’ opinions about this study will be shown, analyzed, and discussed.